2015
DOI: 10.1002/jcp.24832
|View full text |Cite
|
Sign up to set email alerts
|

LIGHT Is a Crucial Mediator of Airway Remodeling

Abstract: Chronic inflammatory airway diseases like asthma and chronic obstructive pulmonary disease are major health problems globally. Airway epithelial cells play important role in airway remodeling, which is a critical process in the pathogenesis of diseases. This study aimed to demonstrate that LIGHT, an inflammatory factor secreted by T cells after allergen exposure, is responsible for promoting airway remodeling. LIGHT increased primary human bronchial epithelial cells (HBECs) undergoing epithelial-mesenchymal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…Understanding this signature may be important for future clinical studies aimed at identifying when LIGHT might be active during human asthma. Another aspect of LIGHT action implied in the aforementioned study of bronchial epithelial cells (44), and also suggested in a separate study of the A549 alveolar epithelial cell line (45), was that LIGHT has a major effect in promoting EMT. These authors showed that LIGHT down-regulated E-cadherin and moderately induced expression of vimentin, again in line with our results, but either did not assess (44), or did not convincingly demonstrate an action on (45), what we consider the cardinal features of EMT, namely induction of collagen, fibronectin, and alpha smooth muscle actin.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Understanding this signature may be important for future clinical studies aimed at identifying when LIGHT might be active during human asthma. Another aspect of LIGHT action implied in the aforementioned study of bronchial epithelial cells (44), and also suggested in a separate study of the A549 alveolar epithelial cell line (45), was that LIGHT has a major effect in promoting EMT. These authors showed that LIGHT down-regulated E-cadherin and moderately induced expression of vimentin, again in line with our results, but either did not assess (44), or did not convincingly demonstrate an action on (45), what we consider the cardinal features of EMT, namely induction of collagen, fibronectin, and alpha smooth muscle actin.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study also partially addressed an inflammatory role for LIGHT in primary bronchial epithelial cells (44). The authors found induction of MMP-9, activin A, CXCL5, and CXCL8, and moderate induction of mRNA for CXCL1, 2, and 3, and ICAM-1, which is largely in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Additional direct effects of LIGHT are also likely to be important. In vitro studies have found that LIGHT can promote some aspects of epithelial‐mesenchymal transition in lung epithelial cells such as downregulation of E‐cadherin and upregulation of fibronectin . Moreover, our recent studies suggest it can also drive proliferation of lung fibroblasts/myofibroblasts that could contribute to increases in smooth muscle mass (da Silva Antunes and Croft, unpublished).…”
Section: Discussionmentioning
confidence: 91%
“…Increasing evidence shows that bronchial epithelial cells orchestrate the pathobiological mechanisms in the pulmonary microenvironment, contributing to airway remodeling, a major pathophysiological change of chronic airway disease. Many studies have shown that bronchial epithelial cells produce inflammatory cytokines and promote proliferation and migration of bronchial smooth muscle cells [8,9,10].…”
Section: Introductionmentioning
confidence: 99%